O sztuce słowa w Potrójnym z Plauta Piotra Cieklińskiego. (Wybrane zagadnienia) - Pirecki, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The article deals with the question of the language and the style of drama Potrójny z Plauta by Piotr Ciekliński. The author of the treatise emphasized the most important components creating the artistic structure of the work, especially regional elements which are so essential for the writings of old literature.